Social Media and Pathology: Where Are We Now and Why Does it Matter?. (September 2017) - Isom, James; Walsh, Meggen; Gardner, Jerad M.
Abstract : Social media has exploded in popularity in recent years. It is a powerful new tool for networking, collaborating, and for the communication and evolution of ideas. It has been increasingly used for business purposes and is now being embraced by physicians including pathologists. Pathology professional organizations and even peer-reviewed pathology journals are now beginning to use social media, as well. There are multiple social media platforms, including Twitter, Facebook, Instagram, LinkedIn, and others. Each platform has different audiences and different ways to share content and interact with other users. This paper discusses the different social media platforms and how they are being used in pathology currently.